Hubungan Implementasi Manajemen Berbasis Sekolah dengan Efektivitas Sekolah Menengah Atas Negeri se-Kota Palangka Raya - Suniati Suniati (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2015)
This research was conducted at State Senior High Schools in Palangka Raya, central Kalimantan, the purpose of this research is to know whether there is any significant relationship between Implementation of school based management toward the school effectiveness at State Senior High Schools in Palangka Raya simultaneously. This research was designed by using the correlation quantitative approach through survey method. Target population are all teachers at State Senior High Schools in Palangka Raya, which amount 163 teachers. The total number of research sample was 115 teachers. Sample was taken by using randomized proportional sampling technique. The result of this research conclude that there was a significant relationship between Implementation of school based management with the School Effectiveness, represented by the linear regression Ŷ= a + bX = 79,85 + 2,57X and correlation coefficient ry = 0.976 which is significant at α = 0,05. This result of this study is expected to be useful for improving the school effectiveness in achieving its vision and mission of the objective of effective and efficient school. It is therefore, necessary to effectively improve school is through the understanding of good teachers in the implementation of school management.